2019
DOI: 10.1155/2019/7309205
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Immunotherapy for Localized and Locally Advanced Renal Cell Carcinoma

Abstract: Systemic therapy strategies in the setting of localized and locally advanced renal cell carcinoma (RCC) have continued to evolve in two directions: as adjuvant therapy (to reduce risk of recurrence or progression in high risk localized groups), or as neoadjuvant therapy as a strategy to render primary renal tumors amenable to planned surgical resection in settings where radical resection or nephron-sparing surgery was not thought to be safe or feasible. In the realm of adjuvant therapy, the results of phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…However, many AGING RCC patients do not have targetable mutations. The emergence of immune checkpoint targets, such as programmed death-1 (PD-1) and programmed deathligand-1 (PD-L1) provides another therapeutic strategy for metastatic RCC [7], perhaps more compelling than targeted therapy agents [8], which emphasizes the importance of the tumor immune status on the outcome of RCC patients. Indeed, various components of the tumor immune microenvironment have been shown to be essential during cancer initiation and progression [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, many AGING RCC patients do not have targetable mutations. The emergence of immune checkpoint targets, such as programmed death-1 (PD-1) and programmed deathligand-1 (PD-L1) provides another therapeutic strategy for metastatic RCC [7], perhaps more compelling than targeted therapy agents [8], which emphasizes the importance of the tumor immune status on the outcome of RCC patients. Indeed, various components of the tumor immune microenvironment have been shown to be essential during cancer initiation and progression [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the RUNX genes are themselves regulated by HIFs, raising the possibility that they are both downstream targets, and act to potentiate the oncogenic signal (43). Molecular characterisation of RCC subtypes revealed that increased immune cell infiltration gene expression signatures associated with the poorest performing patients specifically in ccRCC (4,44,45) and immune checkpoint inhibitors are currently in clinical trial for advanced disease (8,9). In this regard it is interesting that our study reveals a positive correlation between RUNX and local inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 60%
“…Early stage non-metastatic RCC can be treated by partial or radical nephrectomy, however early stage disease is often asymptomatic resulting in patients more commonly presenting with advanced disease which has a much poorer prognosis (6). Standard of care for high risk, advanced metastatic or recurrent RCC involves targeted tyrosine kinase inhibitors (TKI) primarily against the VEGF and mTOR pathways, which have modest improvement over previous cytokine therapies (7,8). Recently, combinatorial use of TKI with immune checkpoint inhibitors against programmed cell death complex (PD1 and PDL1) have shown promising results in stage III clinical trials (9).…”
Section: Introductionmentioning
confidence: 99%
“… 9 There are numerous ongoing/unreported adjuvant or neo-adjuvant trials in RCC involving single immuno-oncology agents or combinations, including atezolizumab, nivolumab alone and with ipilimumab, pembrolizumab, durvalumab and tremelimumab. 18 Final efficacy and safety data from these trials are not yet available. Sunitinib is currently the only agent for adjuvant treatment of RCC approved by the US Food and Drug Administration, 4 but has not been approved by any other regulatory authority.…”
Section: Discussionmentioning
confidence: 99%